(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
total of 314 patients attending skin clinic at Muhimbili Medical Center (MMC) were interviewed about the role of the pharmacist in providing useful information about their diseases and medication. Fifty five percent reported that they knew the role of pharmacy profession. Among those who consulted the Pharmacist concerning their skin diseases and medications, 87% reported to have benefited from the knowledge gained in different aspects, such as, side effects of the drugs (59.5%); drug information (29.9%); what to do with missed dose and/or extra dose taken (86.7%) and awareness of effect of food and cosmetics on their disease and medication (67.6%).